Observation of metallic sphere–complex plasma interactions in microgravity. (20th October 2017) - Schwabe, M; Zhdanov, S; Hagl, T; Huber, P; Lipaev, A M; Molotkov, V I; Naumkin, V N; Rubin-Zuzic, M; Vinogradov, P V; Zaehringer, E; Fortov, V E; Thomas, H M
Abstract: The PK-3 Plus laboratory on board the International Space Station is used to study the interaction between metallic spheres and a complex plasma. We show that the metallic spheres significantly affect both the local plasma environment and the microparticle dynamics. The spheres charge under the influence of the plasma and repel the microparticles, forming cavities surrounding the spheres. The size of the cavity around a sphere is used to study the force balance acting on microparticles at the cavity edge. We show that the ion drag force and pressure force from other microparticles balances with the electric force acting from the sphere to within 20%. At intermediate distances from the sphere surface, the interaction between the microparticles and the metallic spheres is attractive due to the drag force stemming from the ions which are moving towards the highly charged spheres. The spheres thus strongly affect the plasma fluxes. This modification of the plasma flux can lead to an effective surface tension acting on the microparticles, and to the excitation of dust-density waves near the spheres, as the local electric field crosses a threshold.